2022
DOI: 10.1073/pnas.2119644119
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between mutant p53 and p62/SQSTM1 augments cancer cell migration by promoting the degradation of cell adhesion proteins

Abstract: Significance Missense mutations in the TP53 gene, encoding the p53 tumor suppressor, are very frequent in human cancer. Some of those mutations, particularly the more common (“hotspot”) ones, not only abrogate p53’s tumor suppressor activities but also endow the mutant protein with oncogenic gain of function (GOF). We report that p53 R273H , the most common p53 mutant in pancreatic cancer, interacts with the SQSTM1/p62 protein to accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…Among them, several hotspot mutations, including mutations at codons 175, 245, 248 and 273, account for ~30% of p53 mutations in cancers (6)(7)(8)(9)(10). Tremendous studies have demonstrated that in addition to the loss of the tumor-suppressive function of wild-type p53 (wtp53), missense mutp53 proteins often display gain-of-function (GOF) activities to promote tumorigenesis independently of wtp53 through different mechanisms (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Interestingly, while wtp53 proteins are kept at low levels under non-stress conditions mainly through E3 ubiquitin ligase MDM2-mediated ubiquitination and degradation, missense mutp53 proteins often stabilize and accumulate to very high levels in tumors (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, several hotspot mutations, including mutations at codons 175, 245, 248 and 273, account for ~30% of p53 mutations in cancers (6)(7)(8)(9)(10). Tremendous studies have demonstrated that in addition to the loss of the tumor-suppressive function of wild-type p53 (wtp53), missense mutp53 proteins often display gain-of-function (GOF) activities to promote tumorigenesis independently of wtp53 through different mechanisms (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Interestingly, while wtp53 proteins are kept at low levels under non-stress conditions mainly through E3 ubiquitin ligase MDM2-mediated ubiquitination and degradation, missense mutp53 proteins often stabilize and accumulate to very high levels in tumors (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas S100A9, RIPK2, and ACLY are highly expressed in monocytes, it may indicate that these three genes mainly promote the poor prognosis of tumors through the monocytes in tumor tissues. In previous studies, ACLY, SQSTM1, and RIPK2 have already been confirmed to contribute to malignancy by promoting proliferation or EMT in liver cancer cell lines 33–36 …”
Section: Discussionmentioning
confidence: 82%
“…31,32 Therefore, screening immune characters through NAS-based scores lays the foundation for predicting response to immunotherapy. [33][34][35][36] To be noted, the transcriptomic data and qPCR assay revealed that S100A9 was rare in hepatoma cells. By contrast, highly expressed S100A9 was observed in monocyte of the hepatocellular microenvironment based on the single-cell transcriptomic data.…”
Section: Discussionmentioning
confidence: 97%
“…It has been documented that p62 plays important roles in protein degradation either through autophagy and lysosomal targeting or through ubiquitinate proteasomal degradation [ 29 ]. Notably, a recent study has described that the mutp53 R273H -p62 axis participates in driving the ubiquitin-dependent proteasomal degradation of cell junction proteins, such as connexin 43, resulting in cancer cell migration and invasion in PANC-1 cells [ 30 ]. Thus, questions of whether autophagy promotion by HST is related to mutp53 R273H degradation, as well as the mechanism of impaired autophagy induced by HST on SW620 cells, still need to be elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%